Hand-grip isometric strength in judo - Juan G Bonitch-Góngora; Filipa Almeida (Universidad de León, 2014)
<span style="font-family: "Cambria","serif"; font-size: 9pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The grip is an important technical and tactical aspect through which the judokas dominate the adversary, hindering the application of appropriate techniques and favoring their own attack. The judokas must have high levels of isometric force and endurance to this type of force on the gripping muscles of the forearms, as one of the key aspects for success. This article reviews the grip muscular strength and endurance profiles of judokas of different groups (gender, age and competitive level). In general, the peak isometric strength of elite judokas has not changed in the last 40 years and is similar to that reached by non-elite judokas or even registered in large populations. This indicate that the evaluation of the isometric hand grip endurance may be a more relevant parameter than the peak isometric force in judokas, as during the bouts the grip must be maintained for relatively long periods of time and the maximum force cannot be maintained for long. However there are few studies on the ability to resist successive isometric handgrip stress in judokas.